2009
DOI: 10.1007/s11033-009-9864-0
|View full text |Cite
|
Sign up to set email alerts
|

The study of ginsenoside on PPARγ expression of mononuclear macrophage in type 2 diabetes

Abstract: Peroxisome proliferator-activated receptors (PPARs) are transcriptional factors, which play a key role in modulating glucose and lipid metabolism and in the pathogenesis of atherosclerosis. Ginsenosides are the active components of ginseng, which is a perennial aromatic herb that is widely used in China for medicinal purposes. Some studies have reported that ginsenosides have anti-hyperglycemia and anti-obesity effects that involve the PPAR-mediated pathway. The aims of this study were to investigate mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Ot have a number of active ingredients, including anti-inflammatory (Song et al, 2009), anticancer (Chae et al, 2009), antitumor (Mochizuki et al, 1995), antidiabetic (Ni et al, 2010), antihypertensive (Stavro et al, 2005), antifatigue (Lee et al, 2005), and antioxidative effects (Liu et al, 2003). Even though the presence of a number of active ingredients in red ginseng extract is noteworthy, the level of bioavailability of those substances needs to be further improved to be utilized for human health benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Ot have a number of active ingredients, including anti-inflammatory (Song et al, 2009), anticancer (Chae et al, 2009), antitumor (Mochizuki et al, 1995), antidiabetic (Ni et al, 2010), antihypertensive (Stavro et al, 2005), antifatigue (Lee et al, 2005), and antioxidative effects (Liu et al, 2003). Even though the presence of a number of active ingredients in red ginseng extract is noteworthy, the level of bioavailability of those substances needs to be further improved to be utilized for human health benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Rg1 has been recently used to treat type 2 diabetes, as it can improve peroxisome proliferator-activated receptor γ (PPARγ) expression and lipid metabolism [18].…”
Section: Introductionmentioning
confidence: 99%
“…The ginsenoside Rg1 has demonstrated neuroprotective capacity in cerebral ischemia [13, 20], though its molecular underpinnings have not been thoroughly understood. A report in 2010 showed that Rg1 could increase the expression of PPAR γ mRNA, encoding PPAR γ receptors involved in the regulation of a barrage of biological processes including lipid metabolism and the regulation of inflammatory and oxidative responses [12]. Additional evidence has implicated PPAR γ signaling as a contributor to the neurodegenerative processes of cerebral ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…A study in 2010 reported that Rg1 treatment could improve the expression of PPAR γ and lipid metabolism in the treatment of Type 2 diabetes [12]. More recently, the antiapoptotic and anti-inflammatory capacity of a downstream PPAR γ effector has been reported in a rat model of cerebral ischemic injury [13].…”
Section: Introductionmentioning
confidence: 99%